Handbook of research on big data clustering and machine learning - García Márquez, Fausto Pedro (Advances in data mining and database management (ADMDM) book series., 2020)
"This book examines the relationship between the analytic principles of clustering and machine learning to big data. It also explores the connection between engineering/technology and the organizational, administrative, and planning abilities of management"--